Kovels antiques : collectibles price guide 2020 - Kovel, Terry H.; Kovel, Kim (Black Dog & Leventhal Publishers, 2019)
Presents a guide to the most recent prices and photographs for antiques and collectibles, and includes tips on care and identification, cross-references, and record-setting prices.
Included index.
Keywords: Antiques -- Prices; Art objects -- Prices; Antiques; Art objects -- Collectors and collecting; Antiques; Antiques -- Prices; Art objects -- Collectors and collecting; Art objects -- Prices; Catalogs; Catalogs